Investigation of Serum and Leukocyte Ascorbic Acid, Plasma and Intra-Erythrocyte Cholinesterase Levels in Obese Persons - Elif Menekşe (Journal of Contemporary Medicine, 2021)
Obesity is a complicated disease, including excessive amounts of body fat. Obesity is not just an aesthetic problem. It is also a medical issue that increases your risk of other diseases and health conditions, like heart disease, diabetes, and certain cancers. Ascorbic acid (A.A.) produced analog enhancing effects in superoxide generation, DNA strand cutting, and cytotoxicity. In leukocytes, toxicity due to mitochondrial permeability was seen in cells exposed to A.A./peroxynitrite, and these responses were determined to occur independently of Ca2 +. Plasma cholinesterase and erythrocyte acetylcholinesterase activities have a long history of use, both in monitoring workers at risk for organophosphorus pesticide (O.P.) exposure and investigating accidental exposures to O.P.s. Due to the wide variation between individuals, it is necessary to establish unexposed, essential enzyme activities for correct interpretation. Forty-four females and 32 males with a mean age of 40 ± 11.4 years were included in our study. In our study, those with a BMI of 18-24 were considered as control or non-obese (group 1), those between 25 and 30 as obese (group 2), and those between 31 and 42 as extremely obese (group 3). With a moderate standard deviation of 70 and 20 % erosion rate, 76 subjects were determined for 93 % power at the 5 % level of significance. Baseline comparisons among treatment sequences were analyzed using a chi-square test for categorical variables and an unpaired t-test for continuous variables. Mean and standard deviation values were assessed using the SPSS package program, and a statistically significant difference was determined at p-level below 0.05 value. As a result; Although the increase in PCE levels and the decrease in ECE, PTA, and P.A. levels were significantly different. The difference between group 2 and group 3 revealed the importance of these differences between obese and non-obese patients. It has been determined that as obesity increases, the risk of vitamin deficiency also increases.